Characteristics of respiratory viral infections during influenza season in Canadian Hutterite Communities. Issue 6 (19th October 2012) - Kim, Tae H.; Russell, Margaret L.; Fonseca, Kevin; Aoki, Fred; Horsman, Gregory; Van Caeseele, Paul; Chokani, Khami; Voight, Mark; Babiuk, Lorne; Moss, Lorraine; Webby, Richard; Earn, David J. D.; et al.
<x xml:space="preserve">Abstract</x> Please cite this paper as: Kim et al. (2012) Characteristics of respiratory viral infections during influenza season in Canadian Hutterite Communities. Influenza and Other Respiratory Viruses DOI:10.1111/irv.12021. Objectives: To determined the pathogen‐specific incidence of respiratory virus infection in Hutterite communities occurring over the 2008–2009 influenza season and assess temporal characteristics of respiratory illness related to infection. Methods: 3273 participants community members enrolled in a cluster randomized trial of influenza vaccine were studied. Results: One hundred forty‐nine participants had laboratory‐confirmed influenza, and 595 had at least one episode of laboratory‐confirmed respiratory viral infection other than influenza. Entero/rhinovirus had the highest incidence among children <5 years. Conclusions: A decline in the incidence of infections with age was observed for influenza as well as for most other respiratory viruses.